Distribution of nutrients in the O Loan lagoon waters, Phu Yen province (2012–2014) - Vinh, Le Thi; Thu, Nguyen Hong; Tam, Pham Huu; Dung, Le Trong (Vietnam Journal of Marine Science and Technology, 2019)
The results of three surveys in the O Loan lagoon in the dry season (April 2013) and the rainy season (December 2012 and December 2014) showed that in the rainy season the average concentrations of nutrients in waters (ammonium: 76.8 μgN/l, nitrite: 13.9 μgN/l, nitrate: 55 μgN/l and silicate: 4021 μgSi/l) tended to be higher than those in the dry season (ammonium: 6.0 μgN/l, nitrite: 2.6 μgN/L, nitrate: 35 μgN/l and silicate: 1973 μgSi/l) while phosphate concentraiton did not differ between the two seasons with an average concentration of 66.8 μgP/l in rainy season and 60 μgP/L in dry season. By space, the concentrations of nutrients except nitrate in the lagoon, especially in the southern part, were usually higher than those in the canal connected to the sea. At O Loan lagoon waters, only ammonium (mainly in the southern part of the lagoon) and nitrate (mainly in the canal and southern part of the lagoon) concentrations were higher than the criteria values in the rainy season (December 2014) with pollution coefficient of about 1.2. However, the water quality of O Loan lagoon regarding nutrients always still needs to be monitored because from 1992 to the surveyed time, the concentrations of nutrients containing nitrogen and phosphate had the increasing trend in both seasons.